Microbiota Composition and Metabolism Are Associated With Gut Function in Parkinson's Disease. Issue 7 (1st May 2020) - Cirstea, Mihai S.; Yu, Adam C.; Golz, Ella; Sundvick, Kristen; Kliger, Daniel; Radisavljevic, Nina; Foulger, Liam H.; Mackenzie, Melissa; Huan, Tau; Finlay, B. Brett; Appel‐Cresswell, Silke
Abstract: Background: Parkinson's disease is characterized by a high burden of gastrointestinal comorbidities, especially constipation and reduced colonic transit time, and by gut microbiota alterations. The diverse metabolites produced by the microbiota are broadly relevant to host health. How microbiota composition and metabolism relate to gastrointestinal function in Parkinson's disease is largely unknown. The objectives of the current study were to assesses associations between microbiota composition, stool consistency, constipation, and systemic microbial metabolites in Parkinson's disease to better understand how intestinal microbes contribute to gastrointestinal disturbances commonly observed in patients. Methods: Three hundred participants (197 Parkinson's patients and 103 controls) were recruited for this cross‐sectional cohort study. Participants supplied fecal samples for microbiota sequencing (n = 300) and serum for untargeted metabolomics (n = 125). Data were collected on motor and nonmotor Parkinson's symptoms, medications, diet, and demographics. Results: Significant microbiota taxonomic differences were observed in Parkinson's patients, even when controlling for gastrointestinal function. Parkinson's microbiota was characterized by reduced carbohydrate fermentation and butyrate synthesis capacity and increased proteolytic fermentation and production of deleterious amino acid metabolites, including p‐cresol and phenylacetylglutamine. Taxonomic shifts and elevated proteolytic metabolites were strongly associated with stool consistency (a proxy for colonic transit time) and constipation among patients. Conclusions: Compositional and metabolic alterations in the Parkinson's microbiota are highly associated with gut function, suggesting plausible mechanistic links between altered bacterial metabolism and reduced gut health in this disease. The systemic detection of elevated deleterious proteolytic microbial metabolites in Parkinson's serum suggests a mechanism whereby microbiota dysbiosis contributes to disease etiology and pathophysiology. © 2020 International Parkinson and Movement Disorder Society